Bio-inspired fabrication of core@shell structured TATB/polydopamine microparticles via in situ polymerization with tunable mechanical properties. (July 2018) - Lin, Congmei; Gong, Feiyan; Yang, Zhijian; Pan, Liping; Liu, Shijun; Li, Jiang; Guo, Shaoyun
Abstract: Inspired by the strong chemical adhesion of mussels, polydopamine (PDA) was adopted for coating the insensitive high explosive 1, 3, 5-triamino-2, 4, 6-trinitrobenzene (TATB) via a facile in situ polymerization of dopamine on the surface of explosive crystals. A robust and compact core@shell structure was confirmed by field-emission scanning electron microscopy (FESEM), X-ray photoelectron spectroscopy (XPS), and Raman spectra results. After coating, the mechanical strength and toughness were improved with PDA loading, due to the formation of highly effective cross-linked network. With a PDA coating content of 1.5 wt%, the tensile strength and toughness of TATB/PDA composites were 73% and 219% higher than that of the TATB alone, respectively. Compared with TATB/common polymer binder, such as fluoropolymers and polyurethane copolymers, a remarkable enhanced effect was achieved in non-linear creep resistance at different temperatures for TATB/PDA composites with reduced creep strain. The mechanical enhancement mechanism could be originated from strong chemical adhesion of dense and rigid PDA on the crystal surface via in situ polymerization methods. The preparation of explosive composites with core@shell structure by bio-inspired PDA material provides an efficient route for the mechanical enhancement of high explosives. Highlights: We report a novel and general route to coat energetic crystals by polydopamine (PDA). The content of PDA coating could be strictly controlled by adjusting test parameters. The robust and compact core@shell structure was confirmed by spectroscopy and SEM. Formation mechanism of the TATB/PDA microcapsules is proposed. We examine changes in mechanical properties of energetic crystals after PDA coating.